Telling the Truth The Theory and Practice of Documentary Fiction - Foley, Barbara C. (Cornell University Press, 1986)
Barbara Foley here focuses on the relatively neglected genre of documentary fiction: novels that are continually near the borderline between factual and fictive discourse. She links the development of the genre over three centuries to the evolution of capitalism, but her analyses of literary texts depart significantly from those of most current Marxist critics. Foley maintains that Marxist theory has yet to produce a satisfactory theory of mimesis or of the development of genres, and she addresses such key issues as the problem of reference and the nature of generic distinctions. Among the authors whom Foley treats are Defoe, Scott, George Eliot, Joyce, Isherwood, Dos Passos, William Wells Brown, Ishmael Reed, and Ernest Gaines.